The attitude of Elementary Stage Students towards Animation Software as Innovative Strategy to Ensure Learning Outcomes in Mathematics - Pandey, Archana (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Over the period of years, there has been much emphasis on the attainment of minimum levels of learning by the students. The act (RTE- 2009) emphasizes on child friendly learning activities without fear and anxiety. Learning outcomes at elementary stage is a document having list of grade wise learning outcomes. Researchers and policy makers across the globe are interested in improving learning outcomes in fear free environment, with aid of technology and digital innovative. The present paper is an attempt to create Pawtoon (animation software) as innovative strategy to ensure learning outcomes on basis of identifying types of triangle in mathematics at elementary stage. The purpose of this paper is to study the attitude of students towards Pawtoon as improving the learning outcomes. The sample of the study includes 31 VII grade students (15 boys 16 girls) selected in random manner. Findings of the study revealed that both boys and girls showed positive response for pawoon on basis of identifying types of triangle in mathematics. Further, response towards animation software among students is positive. Based on results, conclusions have been drawn that animation software as innovative strategies can ensure learning outcomes in overall holistic and comprehensive manner.